Determination of fumonisins B-1 and B-2 in herbal tea and medicinal plants in turkey by high-performance liquid chromatography - (:unkn) unknown (INT ASSOC FOOD PROTECTION, 2004)
The purpose of this study was to measure the potential levels of fumonisin B-1 (FB1) and fumonisin B-2 (FB2) contamination in several herbal teas and medicinal plants that are consumed regularly in Turkey. FB1 and FB2 were detected using high-performance liquid chromatography with fluorescence detection after derivatization with o-phthaldialdehyde. A total of 115 commercially available herbal tea and medicinal plant samples were analyzed. The recoveries in black tea were 86.9 +/- 8.42% for FB1 and 102 +/- 6.80% for FB2 spiked with 1 mug/g of each analyte. Similarly, the mean recovery results in lime (linden) for FB1 and FB2 were 85.2 +/- 9.76% and 78.6 +/- 5.67%, respectively. The minimum detectable amounts for the o-phthaldialdehyde derivatives of FB1 and FB2 were 0.025 mug/g (1 ng injected) and 0.125 mug/g (5 ng), respectively. FB1 was detected in two samples (0.160 and 1.487 mug/g), and FB2 was detected in none of the samples.
Keywords: CORN-BASED PRODUCTS; FUSARIUM-MONILIFORME; PROCESSED CEREALS; MYCOTOXINS; CONTAMINATION; PULSES; CANCER